2018
DOI: 10.1073/pnas.1801650115
|View full text |Cite
|
Sign up to set email alerts
|

Nontrivial superconductivity in topological MoTe 2− x S x crystals

Abstract: Topological Weyl semimetals (TWSs) with pairs of Weyl points and topologically protected Fermi arc states have broadened the classification of topological phases and provide superior platform for study of topological superconductivity. Here we report the nontrivial superconductivity and topological features of sulfur-doped -phase MoTe with enhanced T compared with type-II TWS MoTe It is found that -phase S-doped MoTe (MoTe S , ∼ 0.2) is a two-band -wave bulk superconductor (∼0.13 meV and 0.26 meV), where the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…For this reason, there is an ongoing effort aimed at achieving superconductivity in such materials and investigating their properties, either through the use of the proximity effect [16,18] or by other means. Successes in this area have been achieved for the type-II Weyl semimetals MoTe 2−x S x [19] and TaIrTe 4 [20], which exhibit intrinsic, exotic superconductivity. For type-I Weyl semimetals, however, such observations are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there is an ongoing effort aimed at achieving superconductivity in such materials and investigating their properties, either through the use of the proximity effect [16,18] or by other means. Successes in this area have been achieved for the type-II Weyl semimetals MoTe 2−x S x [19] and TaIrTe 4 [20], which exhibit intrinsic, exotic superconductivity. For type-I Weyl semimetals, however, such observations are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4(c) shows the temperature evolution of dI/dV spectra measured from 0.4 K to 1.10 K. As the temperature increases, the dip at zero bias is reduced and the gap almost vanishes near 1.10 K, which agrees with the onset T c (1.19 K ~ 1.54 K for different samples) obtained from the electrical transport measurements. The BCS ratio 2Δ(0)/k B T c (k B is the Boltzmann constant)) is estimated about 18.4, which is much larger than that of weak coupling BCS superconductors and reminiscent of the possibility of topological superconductivity [13,40,41]. Magnetic field dependence of dI/dV spectra are shown in Fig.…”
Section: Superconducting Gap and Fermi Arc Surface States Detectementioning
confidence: 95%
“…The chirality of Weyl fermions is responsible for a few novel transport phenomena, such as the chiral anomaly. On the surface of Weyl semimetals, universal signatures of topological Fermi arcs in quasi-particle interference were theoretically predicted [11] and experimentally observed by scanning tunneling microscopy [12,13]. Moreover, the theoretical studies have shown that the presence of superconductivity in Weyl semimetal may lead to a bunch of novel topological phases, including the time-reversal invariant topological superconductor [14], Fulde-Ferrell-Larkin-Ovchinnikov superconductors [15][16][17], and chiral non-Abelian Majorana fermions protected by second Chern numbers [18].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, chemical pressure is introduced in our case when partial larger Te 2-(2.21 Å) is substituted by Se 2-(1.98 Å)49 . Therefore, the enhancement of T c may be explained by calculating pressure-induced larger superconductivity pairing energy44 . To solidify this assumption, systematic magneto-transport measurements are conducted on pristine T d -MoTe 2 and MoSe x Te 2-x with x=0.95 thin films under a perpendicular filed at different temperatures.…”
mentioning
confidence: 99%